DIAGNOSIS AND TREATMENT OF SINUSITIS OCCURRING IN HOT CLIMATES (World Bulletin of Public Health, 2024)
The nasal cavity and its mucous membrane as an object of research from a functional and morphological point of view, the human respiratory system consists of tissues and organs that provide pulmonary ventilation and pulmonary respiration. The airways include: nose, nasal cavity, nasopharynx, larynx, trachea, bronchi and bronchioles. The nose and nasal cavity serve as conductive channels for air, in which it is heated, moistened and filtered, olfactory receptors are enclosed here, and, in addition, the nasal cavity is the first barrier to protect the lower respiratory system. By the septum nasi nasal septum (bony at the back and cartilaginous at the front), the nasal cavity is divided into two symmetrical halves, which communicate with the atmosphere from the front through the outer nose with the help of nostrils.
Keywords: allergic rhinitis; bronchial asthma; glucocorticosteroid; otorhinolaryngology